The Administrative and Political Developments in Aqaba and Ma'an Districts between 1917-1925 "Documentary study" - & Nidal Al-Momani; Ibrahim Al-Shraah (My University, 2014)
This study aimed to uncover the conditions of Aqaba and Ma'an districts during the first quarter of the twentieth century, because of their importance in terms of their geographical location in the south of Jordan, and to the north of Hijaz, near the Red Sea. The focus was on the administrative conditions in both districts since the end of Ottoman regime and during the Arab Hashemite regime in Hijaz, and what several administrative developments occurred in Aqaba and Ma'an until they were attached to the Emirate of Transjordan in 1925. This study also highlighted the political circumstances which accompanied attaching both districts to the Emirate of Transjordan and the attitudes of both the British and Najdi governments towards this because a new era began in Aqaba and Ma'an in the Emirate of Jordan since the mid-twenties. The study was based on a variety of resources, namely, the British documents, news reported by Al-Qibla Newspaper about these two districts during the Hashemite regime, and other resources.

هدفت هذه الدراسة إلى الكشف عن أوضاع قضائي العقبة ومعان خلال الفترة الممتدة من نهاية الحرب العالمية الأولى حتى أواسط العشرينات، لما لهذين القضائين من أهمية، من حيث موقعهما الجغرافي في جنوبي الأردن، ووقوعهما إلى الشمال من الحجاز وبالقرب من البحر الأحمر. وقد تمّ التركيز على الأوضاع الإدارية في القضائين منذ نهاية الحكم العثماني وخلال الحكم العربي الهاشمي في الحجاز، وما طرأ على العقبة ومعان من استحداثات إدارية عديدة حتى إلحاقهما بإمارة شرقي الأردن في عام 1925. وقد بيّنت الدراسة الظروف السياسية التي رافقت إلحاق قضائي العقبة ومعان بإمارة شرقي الأردن، وموقف كل من السلطات: البريطانية والنجدية من تبعية القضائين لإمارة شرقي الأردن؛ إذ بدأ عهد جديد للعقبة ومعان في الإمارة الأردنية منذ أواسط العشرينات. وقد استندت الدراسة على مجموعة متنوعة من المصادر من أبرزها: الوثائق البريطانية المنشورة وغير المنشورة، وما أوردته صحيفة القبلة الحجازية من أخبار عن القضائين أثناء الحكم الهاشمي لهما؛ بالإضافة إلى مصادر ومراجع أخرى لها علاقة بموضوع الدراسة.
التطورات الإدارية والسياسية في قضائي العقبة ومعان بين عامي (1917 – 1925) "دراسة وثائقية"